Journal: Blasting in the New Millennium: Blasters Take on the Role of Blast Site Manager - Steve Dillingham (International Society of Explosives Engineers, 2001)
Today, a typical blaster is likely to wear many hats, including, but not limited to, supervisor, risk manager, safety coordinator, explosives engineer, communicator, as well as professional decision maker. Simply put, a blaster in the new millennium is an all encompassing blast site manager. As you know, accidents on the blast site can range from blast crew injuries to blasting incidents resulting from vibration, flyrock, misfires, etc. Not surprising, the incidents can quite often be traced back to direct preventable human action on the blast site. They can, however, frequently be avoided, if responsibly identified early and managed properly by an efficient blast site manager. Your company cannot afford to simply employ blasters; good blast site managers are necessary to produce the safest results possible.